CROSS-CULTURAL ADAPTATION OF THE INTEGRARE SCALE INTO BRAZILIAN PORTUGUESE - Vidor, Isabella Duarte; Bavaresco, Taline; Silva, Ana Carolina Fioravanti Eilert da; Santos, Cássia Teixeira dos; Gálvez, Ana María Porcel; Lucena, Amália de Fátima (Cogitare Enfermagem, 2024)
Objective: to carry out the cross-cultural adaptation and evaluation of the psychometric properties of the INTEGRARE Scale for Brazilian Portuguese. Method: methodological study with translation, synthesis, back-translation, and expert review stages. The psychometric properties were assessed for reliability, content validation and convergent construct validation with the Braden Scale. The pre-test was carried out with 30 patients and the validation with 120 adult patients admitted to the clinical and surgical units of a university hospital in southern Brazil. Results: the INTEGRARE Scale was easy to apply and understand, proving to be applicable in Brazil. In the analysis of the psychometric reliability properties, internal consistency was identified with questionable Cronbach’s alpha (α=0.63); however, in convergent validity there was a significant, positive, and strong correlation (Rho=0.741; p<0.001) in relation to Braden. Conclusion: the adaptation broadens the scope of nursing in the use of instruments that predict the risk of Pressure Injury.